BetaSys systems biology of regulated exocytosis in pancreatic ß-Cells - Booß-Bavnbek, Bernhelm; Klösgen, Beate; Larsen, Jesper; Pociot, Flemming; Renström, Erik; SpringerLink (Online service). (New York Springer, 2011)
Uses the example of regulated exocytosis in pancreatic β-cells, and its relevance to diabetes, to illustrate the major concepts of systems biology, its methods and applications. In using a focused approach here by picking one outlook, the topic of Systems Biology is made more accessible.Systems Biology is a fast moving field, but the work presented here emphasizes the principal aspects of the field, making this a tool for on-going research. The insulin secreting β-cell is one of the most specialized cell types with diverse and multi-functional components (genes, gene products, organelles and metabolites) and a multitude of regulatory strategies in response to internal and environmental signals. This book looks at the technological advances that make simultaneous detection of thousands of biological variables possible; at a substantial variety of mathematical models and numerical simulations that aim to explain major aspects of the β-cell function; and at the challenge to formulate a comprehensive and robust model of the main networks of the underlying biochemical and physical processes for diagnostic and therapeutic use
Preface -- Systems biology of ?-cells - revisited -- Established facts and open questions of the focused systems analysis of regulated exocytosis in ?-cells ? a background for a focused systems analysis approach -- Mitochondria and metabolic signals in ?-cells -- ?-cell ontogenesis and the insulin production apparatus -- The role of the cytoskeleton in transport and release of the insulin-containing granules by pancreatic ?-cells -- The mathematical microscope making the inaccessible accessible -- Magnetic resonance imaging of pancreatic ?-cells -- Mapping the ?-cell in 3D at the nanoscale using novel cellular electron tomography and computational approaches -- In vivo applications of inorganic nanoparticles -- Cell cultivation and sensor-based assays for dynamic measurements of cell vitality: basic concepts -- Bioimpedance spectroscopy -- DNA variations, impaired insulin secretion and type-2 diabetes -- Genetically programmed defects in ?-cell function -- Proteomic analysis of the pancreatic islet ?-cell secretory granule: current understanding and future opportunities -- Physiological and pathophysiological role of islet amyloid polypeptide (IAPP, amylin) - a role in the pathogenesis of type-2 diabetes -- Present state of islet transplantation for type-1 diabetes patients -- Predictive protein networks and identification of drugable targets in the ?-cell -- Nanotoxicity -- From silicon cell to silicon human -- Probing cellular dynamics with mesoscopic simulations -- What drives calcium oscillations in ?-cells? new tasks for cyclic analysis -- Whole-body and cellular models of glucose-stimulated insulin secretion -- Geometric and electromagnetic aspects of fusion pore making -- Index.
Title from title screen (viewed September 29, 2023)
Electronic reproduction
Keywords: Exocytosis; Systems biology